ASMR amplifies low frequency and reduces high frequency oscillations. (April 2022) - Swart, Thomas R.; Banissy, Michael J.; Hein, Thomas P.; Bruña, Ricardo; Pereda, Ernesto; Bhattacharya, Joydeep
Abstract: Autonomous sensory meridian response (ASMR) describes an atypical multisensory experience of calming, tingling sensations in response to a specific subset of social audiovisual triggers. To date, the electrophysiological (EEG) correlates of ASMR remain largely unexplored. Here we sought to provide source-level signatures of oscillatory changes induced by this phenomenon and investigate potential decay effects—oscillatory changes in the absence of self-reported ASMR. We recorded brain activity using EEG as participants watched ASMR-inducing videos and self-reported changes in their state: no change (Baseline); enhanced relaxation (Relaxed); and ASMR sensations (ASMR). Statistical tests in the sensor-space were used to inform contrasts in the source-space, executed with beamformer reconstruction. ASMR modulated oscillatory power by decreasing high gamma (52–80 Hz) relative to Relaxed and by increasing alpha (8–13 Hz) and decreasing delta (1–4 Hz) relative to Baseline. At the source level, ASMR increased power in the low-mid frequency ranges (8–18 Hz) and decreased power in high frequency (21–80 Hz). ASMR decay effects reduced gamma (30–80 Hz) and in the source-space reduced high-beta/gamma power (21–80 Hz). The temporal profile of ASMR modulations in high-frequency power later shifts to lower frequencies (1–8 Hz), except for an enhanced alpha, which persists for up to 45 min post self-reported ASMR. Crucially, these results provide the first evidence that the cortical sources of ASMR tingling sensations may arise from decreases in higher frequency oscillations and that ASMR may induce a sustained relaxation state.